A New Popular Front, or, on the Role of Critical Jurisprudence under Neo-Authoritarianism in Central-Eastern Europe - Tacik, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The current decade brought a neo-authoritarian wave to the countries in CEE. This process, which in certain respects runs parallel to the populist upsurge in Western countries, has its own specificity. Firstly, by focusing on the clash between “elites” and “the people”, it rekindles – in a displaced, right-wing form – the class conflict which before 1989 was an ideological staple in CEE countries. Secondly, insofar as neo-authoritarianism in CEE has often a distinctly neo-liberal agenda shadowed by declarative anti-globalism and national chauvinism, it warps the field of political struggle. Thirdly, in the neo-authoritarian turn law becomes the crucial field of ideological fight, principally in those countries where populists came to power. In this respect, new governments in CEE resort to a blend of old Fascist tools (such as dismantling of constitutional control and denying the primacy of international law) and new inventions (such as the effective state of exception in some areas of law in Poland introduced in 2015–18). The role of critical jurisprudence in CEE is therefore particularly significant and difficult. The paper argues that liberal jurisprudence, although actively engaged in analysing neo-authoritarianism, does not possess adequate conceptual tools for full success. Therefore critical jurisprudence should urgently take part in explaining neoauthoritarianism in the legal field.